Perbedaan Derajat Adhesi Peritendinous Setelah Pemberian Platelet Rich Plasma (PRP) Terhadap Penyembuhan Ruptur Tendon Achilles Tikus Wistar - Ananda, Gita Putri; Rahmadian, Rizki; Intan, Shinta Ayu; Rikarni, Rikarni; Rusjdi, Selfi Renita (Faculty of Medicine, Universitas Andalas, 2025)
Platelet-rich plasma (PRP) has been identified as a potential agent to enhance the tendon healing process and prevent complications such as adhesion and tendon displacement after surgery. Objective: To determined the difference in the degree of peritendinous adhesion after administration of platelet-rich plasma (PRP) on the healing of Achilles tendon rupture in Wistar rats. Methods: This study used a post-test only control group experimental design. Tendons in the control group were treated without PRP, while the treatment group received PRP before care. After one week, the degree of peritendinous adhesion was evaluated microscopically using the Tang scoring system. Results: The mean degree of adhesion in the control group was 3.38, and in the treatment group it was 3.83. The independent t-test yielded a non-significant value of 0.411 (p > 0.05). Conclusion: There was no significant difference in the degree of peritendinous adhesion in Achilles tendon rupture healing of Wistar rats between the group given PRP and the group not given PRP. Keywords: peritendinous adhesion, PRP, tendon rupture, Tang score